‘Tis Pity She’s (Still) a Whore: Mary Magdalene in The Chosen - Burnette-Bletsch, Rhonda (Journal for the study of the historical Jesus, 2022)
Early Jesus films reveled in the traditional, historically inaccurate interpretation of Mary Magdalene as a penitent prostitute. While films produced since the 1980s are less heavy-handed in explicitly sexualizing or shaming Mary, promiscuity remains her most persistent trait. Traces of the penitent prostitute are detectable in The Chosen, a crowd-funded evangelical series on the life of Jesus which foregrounds Mary as a disciple. Her story arc in The Chosen mirrors that of the prostitute protagonist in Redeeming Love (2022), another evangelical film based on Francine River’s fictional adaptation of the Hosea/Gomer story. Both works adhere closely to what film scholar, Russell Campbell, identifies as the ‘martyr’ character type and ‘love story’ narrative structure commonly found in cinematic depictions of sex work. Ultimately, these films reinscribe patriarchal ideology when the woman is rescued and reformed by a virtuous man at risk of his own reputation.